(untitled) (AYUSHDHARA, 2023)
Yakruth plays an important role in the Chayapachay and Ranjana of Rasa Dhatu. Yakruth and Pleeha are formed by the Raktadhatu. Yakruth is situated at the Dakshina bhaga and Pleeha at the Vaama bahga. Yakruth and Pleeha are the Moola Sthana of the Raktavaha Srothas. Madya is considered as alcohol it’s having qualities of Amla Usha laghu Tikshna, Sukshma, Vyavayi Ruksha Vikasi and Vishada. Madya vitiates Pitta as well as Rakta and that leads to Yakruth Vriddi. Rakta is one of the main Dushyas in Yakruth Vriddi. Diet and lifestyle are major factors that influence susceptibility to liver disorders. Alcohol use is quite common in India. According to recent data published by NHPI 74% of men and 48% of women are alcoholics. Alcohol disorders cover the spectrum of disorders beginning from the fatty liver, jaundice, hepatomegaly, ascites, and cirrhosis advanced and irreversible forms of liver injury related to the consumption of alcohol. There are three histopathological stages of alcoholic liver disease alcoholic fatty liver, alcoholic hepatitis, and, alcoholic cirrhosis. These alcoholic liver disorders’ pathogenesis can be understood in Ayurveda with the help of Kamala, Yakruth Vriddhi, Shchutha, and Ashchutha Yakruthodara. Hence an attempt is made to understand the etiopathogenesis of ALD w.s.r Yakruth Vriddi.